Stability Analysis of an Integrated Offshore Wind and Seashore Wave Farm Fed to a Power Grid Using a Unified Power Flow Controller - Wang, Li; Li, Hao-Wen; Wu, Cheng-Tai (IEEE transactions on power systems, 2013)
This paper presents the analyzed results of an integrated offshore wind and seashore wave farm fed to an onshore power grid through a unified power flow controller (UPFC) to simultaneously achieve power-fluctuation mitigation and stability improvement. The performance of the studied offshore wind farm (OWF) is simulated by an equivalent aggregated 100-MW doubly-fed induction generator (DFIG) while the characteristics of the studied seashore wave farm (SWF) are simulated by an equivalent aggregated 60-MW squirrel-cage induction generator (SCIG). A damping controller of the proposed UPFC is designed by using modal control theory to render adequate damping characteristics to the studied system. A frequency-domain approach based on a linearized system model using eigenvalue analysis and a time-domain scheme based on a nonlinear system model subject to disturbance conditions are systematically carried out. It can be concluded from the simulation results that the proposed UPFC joined with the designed damping controller can effectively stabilize the studied integrated OWF and SWF under various disturbance conditions. The inherent power fluctuations injected to the power grid can also be effectively mitigated by the proposed control scheme.